Effect of salbutamol on lung function and chest wall volumes at rest and during exercise in COPD. Issue 11 (30th June 2005) - Aliverti, A; Rodger, K; Dellacà, R L; Stevenson, N; Lo Mauro, A; Pedotti, A; Calverley, P M A
Abstract : Background: Inhaled bronchodilators can increase exercise capacity in chronic obstructive pulmonary disease (COPD) by reducing dynamic hyperinflation, but treatment is not always effective. This may reflect the degree to which the abdomen allows dynamic hyperinflation to occur. Method: A double blind, randomised, crossover trial of the effect of 5 mg nebulised salbutamol or saline on endurance exercise time was conducted in 18 patients with COPD of mean (SD) age 67.1 (6.3) years and mean (SD) forced expiratory volume in 1 second (FEV1 ) of 40.6 (15.0)% predicted. Breathing pattern, metabolic variables, dyspnoea intensity, and total and regional chest wall volumes were measured non-invasively by optoelectronic plethysmography (OEP) at rest and during exercise. Results: Salbutamol increased FEV1, forced vital capacity (FVC) and inspiratory capacity and reduced functional residual capacity (FRC) and residual volume significantly. OEP showed the change in resting FRC to be mainly in the abdominal compartment. Although the mean (SE) end expiratory chest wall volume was 541 (118) ml lower (p<0.001) at the end of exercise, the endurance time was unchanged by the bronchodilator. Changes in resting lung volumes were smaller when exercise duration did not improve, but FEV1 still rose significantly after active drug. After the bronchodilator these patients tried to reduce the end expiratory lung volume when exercising, while those exercising longer continued to allow end expiratory abdominal wall volume to rise. The change to a more euvolumic breathing pattern was associated with a lower oxygen pulse and a significant fall in endurance time with higher isotime levels of dyspnoea. Conclusions: Nebulised salbutamol improved forced expiratory flow in most patients with COPD, but less hyperinflated patients tried to reduce the abdominal compartmental volume after active treatment and this reduced their exercise capacity. Identifying these patients has important therapeutic implications, as does an understanding of the mechanisms that control chest wall muscle recruitment.